Gradient Porous Elastic Hydrogels with Shape‐Memory Property and Anisotropic Responses for Programmable Locomotion. (26th October 2015) - Luo, Rongcong; Wu, Jin; Dinh, Ngoc‐Duy; Chen, Chia‐Hung
Abstract : Programmable locomotion of responsive hydrogels has gained increasing attention for potential applications in soft robotics, microfluidic components, actuators, and artificial muscle. Modulation of hydrogel pore structures is essential for tailoring their mechanical strength, response speeds, and motion behaviors. Conventional methods forming hydrogels with homogeneous or stepwise‐distributed pore structures are limited by the required compromise to simultaneously optimize these aspects. Here, a heterobifunctional crosslinker enabled hydrothermal process is introduced to synthesize responsive hydrogels with well‐defined gradient pore construction. According to gradient porosity controls, the hydrogels simultaneously exhibit rapid responses to external stimuli, high elasticity/compressibility, and programmable locomotion capability. By incorporating polypyrrole nanoparticles as photothermal transducers, photo/thermal responsive composite hydrogels are formed to enable programmable control of locomotion such as bending, curving, twisting, and octopus‐like swimming under near‐infrared laser stimulation. The tunable pore structures, mechanical properties, and locomotion of this new class of materials make these gradient porous hydrogels potentially suitable for a variety of applications. Abstract : Gradient porous elastic hydrogels with rapid and programmable locomotion to thermal‐/photostimulation are obtained through an effective hydrothermal route. According to the gradient porosity control, the hydrogels simultaneously exhibit rapid responses, high elasticity, and anisotropic locomotion. The hydrothermally induced hydrogelation mechanism is applicable to other thermal‐responsive monomers and crosslinkers, opening new avenues for modulating the pore structures of soft materials.